Legal Protection Against the Transfer of Fiducia Rights in the Takeover of Creditors - Suwarno, Ernawati; Suriaatmadja, Toto Tohir; Kurrohman, Taufik (Yayasan Sinergi Kawula Muda, 2026)
Fiduciary security is a form of collateral over property or material security over movable objects, both tangible and intangible, which remain in the control of the fiduciary. This means that the pledged object is not physically handed over to the beneficiary, but the security right over it is recorded through a deed and registered at the fiduciary registration office. The construction of a fiduciary guarantee is the transfer of property rights in trust, over the debtor's property or movable goods to the creditor with physical control over the goods remaining with the debtor. Provided that if the debtor repays the debt in accordance with the stipulated time, the creditor is obliged to return the title to the property or goods to the debtor. In the repertoire of legal science, the transfer of property like this is called